(untitled) (Prilozi za književnost, jezik, istoriju i folklor, 2023)
Grzegorz Łatuszyński (1933-2020) was undoubtedly one of the finest Polish translators of 20th century Serbian poetry. Apart from 16 volumes devoted to poems by selected authors, he also published two-volume anthology presenting poems by 155 Serbian poets. Even an on surface analysis of the translations proves Łatuszyński’s ability to combine his poetic sensitivity with philological precision. Grzegorz Łatuszyński also translated two important novels (by Miloš Crnjanski and Borislav Pekić) as well as a book of letters by Filip David and Mirko Kovač. Each volume of Łatuszyński’s translations is accompanied by a biographical profile of the poets and some characteristics of their work. Another aspect of Łatuszyński professional profile is essay writing and journalism. Besides, he translated Polish poetry into Serbian. All Łatuszyński’s professional activities has led to a closer cooperation between Polish and Serbian literary circles.